Supplemental Plant Extracts From Flos lonicerae in Combination With Baikal skullcap Attenuate Intestinal Disruption and Modulate Gut Microbiota in Laying Hens Challenged by Salmonella pullorum - Wang, Wei-wei; Jia, Hong-jie; Zhang, Hai-jun; Wang, Jing; Lv, Hui-yuan; Wu, Shu-geng; Qi, Guang-hai (Frontiers in Microbiology, 2019)
Dietary inclusions of baicalin and chlorogenic acid were beneficial for intestinal health in pigs. Nevertheless, it is unknown whether these plant-derived products had protection for intestine against bacterial challenge in chickens. This study was aimed at evaluating the potential mitigating effects of plant extracts (PE) from Flos lonicerae combined with Baikal skullcap (the active components are chlorogenic acid and baicalin) on intestinal disruption and dysbacteriosis induced by Salmonella pullorum in laying hens. A total of 216 41-wk-old layers were randomly divided into 3 groups (6 replicates per group): negative control (NC), S. pullorum-infected positive control (PC), and the S. pullorum-infected group with supplementation of PE at 1000 mg/kg. All birds except those in NC were challenged with S. pullorum at the end of 4 wk of the experiment. S. pullorum challenge impaired (P < 0.05) the production performance (egg production, feed intake and feed efficiency) of laying hens, increased (P < 0.05) serum endotoxin content and frequency of Salmonella-positive organs, as well as up-regulated (P < 0.05) ileal expression of pro-inflammatory cytokines including IFNG, TNFA, IL8 and IL1B, whereas PE addition reversed (P < 0.05) these changes and increased (P < 0.05) ileal IL10 expression. Supplemental PE moderated ileal microbiota dysbiosis in challenged birds, characterized by a reduced abundance of Firmicutes along with increased abundances of Bacteroidetes (Bacteroides), Deferribacteres and several butyrate-producers such as Prevotellaceae, Faecalibacterium, Blautia, Butyricicoccus and Lachnoclostridium and Olsenella, which may assist with energy harvesting and boost anti-inflammatory capacity of host. The decreased abundance of Firmicutes with the increased abundance of Bacteroidetes caused by PE addition had positive correlations with the decreased expression of ileal pro-inflammatory cytokines. The increased abundances of Bacteroidetes (Bacteroides) and Prevotellaceae following PE addition were also positively correlated with the improvement of performance (egg production and feed intake) of laying hens. Collectively, supplemental PE from Flos lonicerae in combination with Baikal skullcap alleviated S. pullorum-induced intestinal disruption and performance impairment in laying hens, which could be at least partially responsible by the modulation of gut microbial composition.